Langerhans cells and NK cells cooperate in the inhibition of chemical skin carcinogenesis. (1st February 2017) - Ortner, Daniela; Tripp, Christoph H.; Komenda, Kerstin; Dubrac, Sandrine; Zelger, Bernhard; Hermann, Martin; Doppler, Wolfgang; Tymoszuk, Piotr Z.; Boon, Louis; Clausen, Björn E.; Stoitzner, Patrizia
ABSTRACT: Tissue immunosurveillance is an important mechanism to prevent cancer. Skin treatment with the carcinogen 7, 12-dimethylbenz(a)anthracene (DMBA), followed by the tumor promoter 12-O-tetra-decanoyl-phorbol-13-acetate (TPA), is an established murine model for squamous cell carcinoma (SCC). However, the innate immunological events occurring during the initiation of chemical carcinogenesis with DMBA remain elusive. Here, we discovered that natural killer (NK) cells and Langerhans cells (LC) cooperate to impair this oncogenic process in murine skin. The depletion of NK cells or LC caused an accumulation of DNA-damaged, natural killer group 2D-ligand (NKG2D-L) expressing keratinocytes and accelerated tumor growth. Notably, the secretion of TNFα mainly by LC promoted the recruitment of NK cells into the epidermis. Indeed, the TNFα-induced chemokines CCL2 and CXCL10 directed NK cells to DMBA-treated epidermis. Our findings reveal a novel mechanism how innate immune cells cooperate in the inhibition of cutaneous chemical carcinogenesis.